Spatial and temporal trends in poly- and per-fluorinated compounds in the Laurentian Great Lakes Erie, Ontario and St. Clair. (June 2018) - Codling, Garry; Sturchio, Neil C.; Rockne, Karl J.; Li, An; Peng, H.; Tse, Timothy J.; Jones, Paul D.; Giesy, John P.
Abstract: The temporal and spatial trends in sediment of 22 poly- and perfluorinated (PFAS) compounds were investigated in the southern Great Lakes Erie and Ontario as well as Lake St. Clair. Surface concentrations measured by Ponar grab samples indicated a trend for greater concentrations near to urban sites. Mean concentrations ∑22 PFAS were 15.6, 18.2 and 19 ng g −1 dm for Lakes St. Clair, Erie and Ontario, respectively. Perfluoro-n-butanoic acid (PFBA) and Perfluoro-n-hexanoic acid (PFHxA) were frequently determined in surface sediment and upper core samples indicating a shift in use patterns. Where PFBA was identified it was at relatively great concentrations typically >10 ng g −1 dm. However as PFBA and PFHxA are less likely to bind to sediment they may be indicative of pore water concentrations Sedimentation rates between Lake Erie and Lake Ontario differ greatly with greater rates observed in Lake Erie. In Lake Ontario, in general concentrations of PFAS observed in core samples closely follow the increase in use along with an observable change due to regulation implementation in the 1970s for water protection. However some of the more water soluble PFAS were observed in deeper core layers than the time of production could account for, indicating potential diffusion within the sediment. Given the greater sedimentation rates in Lake Erie, it was hoped to observe in greater resolution changes since the mid-1990s. However, though some decrease was observed at some locations the results are not clear. Many cores in Lake Erie had clearly observable gas voids, indicative of gas ebullition activity due to biogenic production, there were also observable mussel beds that could indicate mixing by bioturbation of core layers. Graphical abstract: Image 1 Highlights: The two most contaminated lakes were studied for PFAS in sediment. Lake St Clair and the west of Lake Erie was most contaminated in surface samples. Temporal trends in Lake Ontario follow expected use patterns for most PFAS. Lake Erie temporal trends less defined due to multiple factors. Urban sites appear the primary sources for Ponar sediment samples. Abstract : This publication looks at the spatial and temporal trends in PFAS in the sediment of Lake Erie, Ontario and St Clair. Temporal trends are assessed through multiple core samples taken across the lake while spatial variation is from a greater number of surface sediment Ponar samples to provide greater resolution. Temporal trends mostly identify an increase in PFAS in sediment with time. However, more water-soluble compounds have been measured at depths greater than use would cause and may imply that for some PFAS cores are not ideal sample tools.